Modelización de la calidad del agua del estero El Pital, cantón Quevedo, estación seca, año 2018 - García Figueroa, Jazmín Margarita (2018)
The current The pital is a body of water that is part of the water network of the province of Los Ríos, which crosses the urban area of the city of Quevedo and ends at the Quevedo River. The current is the receiving source of a point discharge from a fruit processor, and two tributaries, one from the Promejoras Sector and the other being an eye of water that is born from the Gustavo Campi sector. The objective of this research was to model the water quality of the El Pital estuary in the dry season and as specific objectives: (1) determine the hydromorphological characteristics of the current The Pital, (2) characterize the water quality of the El Pital estuary, (3) model the water quality of the current El Pital with the Streeter-Phelps model, and, (4) simulate the water quality of El Pital stream with the QUAL2K computer program. The characterization of the physicochemical parameters of water quality was carried out, which were: Biochemical oxygen demand (BOD), dissolved oxygen (DO), hydrogen potential (pH), temperature (° C) and electrical conductivity (CE). Seven sampling points were established: section 1, section 2, section 3, upstream of section 1, main discharge and the two tributaries identified, with 8 biweekly repetitions of sampling campaigns during the months of July, August, September and October, considered dry season. The applied mathematical model was based on the Streeter-Phelps equations, which allowed the water quality of the El Pital stream to be modeled to obtain the BOD and DO profiles, where in the first stay the constants were obtained by applying the respective mathematical equations , to then calibrate the kinetic constants of reaaction (Ka), deoxygenation (Kd) and total removal of the BOD (Kr) using the statistical software Statgraphics using the Monte Carlo simulation tool, obtaining 10,000 possible variations of the kinetic constants. Finally, the simulation of water quality was carried out using the QUAL2K program, entering the hydrodynamic information of the stream and the calibrated constants.